The Influence of Tuition Fee Determination and Study Program Quality on Interest in Selecting Private Universities Among Prospective Students (Empirical Study in East Jakarta) - Suryani, Neneng; Nabilah, Lily; Ependi (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
The purpose of this study is to analyze the influence of the determination of education costs and the quality of study programs on the interest in choosing private universities among prospective students (an empirical study in East Jakarta). This research method is quantitative descriptive, while the data used is quantitative primary data, the population is 243,352 people using the Slovin formula, a sample of 100 people is obtained, the data collection technique is carried out with a questionnaire using a Likert scale of 1-5, while the data analysis method is descriptive data analysis and statistical data analysis. The results of the significance and linear regression research can be concluded that the linear regression results of Interest in Choosing Private Universities = 3.412 + 0.638 Determination of Tuition Fees + 0.614 Quality of Study Programs, are very positive and significant and linear and the results of the test are the regression coefficient on the Cost Determination variable, namely 0.638. The results of the hypothesis test, through the t test, show that the calculated t value> t table (3.262> 1.660) and a significance value of 0.002 <0.05. The Cost Determination variable shows a positive and significant influence and the Quality of Study Programs variable shows a positive and significant influence based on the results of the t test, it can be seen that the calculated t value> t table (8.452> 1.660) and a significance value of 0.000 <0.05. The results of the hypothesis test, through the F test, show that the calculated F value (175.963)> F table (3.09). This can be strengthened by a significance value of 0.000 < 0.05, there is a positive and significant influence simultaneously between the determination of education costs and the quality of study programs on interest in choosing private universities.